2016
DOI: 10.18203/2320-6012.ijrms20164535
|View full text |Cite
|
Sign up to set email alerts
|

Hematological profile including alkali resistant hemoglobin of neonates at birth using cord blood in relation to gestational age and maternal diseases

Abstract: Background: The importance of complete hemogram along with the hematological indices in the diagnosis of neonatal health cannot be overemphasized. There is a severe paucity of relevant data regarding neonatal hematological profile in relation to gestational age and maternal diseases in this part of the country. With this perspective, the authors intended to do a pilot study to analyse the haematological profile of neonates of different gestational ages and different maternal diseases born in a teriary care hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In addition, fetal-maternal blood exchange, through the umbilical cord, may also contribute to Lawton et al (2015), reported that newborn blood volume increases when umbilical cord clamping is not done immediately after childbirth. Such results concerning erythrocyte parameters in newborns are also reported by Bhattacharya et al (2017). In addition, the mean values of leukocytes, eosinophils, lymphocytes and monocytes of the newborns were significantly higher (p<0.01) than those of women at childbirth.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, fetal-maternal blood exchange, through the umbilical cord, may also contribute to Lawton et al (2015), reported that newborn blood volume increases when umbilical cord clamping is not done immediately after childbirth. Such results concerning erythrocyte parameters in newborns are also reported by Bhattacharya et al (2017). In addition, the mean values of leukocytes, eosinophils, lymphocytes and monocytes of the newborns were significantly higher (p<0.01) than those of women at childbirth.…”
Section: Discussionsupporting
confidence: 74%